Persepsi Generasi Y Terhadap Kerajinan Tangan Daerah - Hazmanan Pasaribu; Chali Rafi; Khairawati Khairawati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
At this juncture, the growth of handicraft business in the world is quite rapidly which marked by the hard competition increasingly of handicraft products between the district of regions Aceh, therefore the handicraft entrepreneurs from Aceh must show a high competitiveness to other regional products through conduct a good marketing strategy. “Y” generation is an important consumer market segment in future due to the rapid growth of this generation and is also a high-income community. Consequently, the